2011
DOI: 10.1159/000331917
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the Subjective Benefit of Electric Acoustic Stimulation with the Abbreviated Profile of Hearing Aid Benefit

Abstract: Conclusion: This study demonstrates that electric-acoustic stimulation (EAS) significantly decreases the subjective impairment in speech perception. Objectives: To assess the subjective benefit of EAS over the first 12 months after EAS fitting using the Abbreviated Profile of Hearing Aid Benefit (APHAB). Method: Twenty-three EAS users, implanted with either the PULSARCI100 FLEXEAS provided with the DUET EAS processor or the COMBI40+ Medium provided with the TEMPO+ speech proces… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…Given that the expected low-frequency threshold elevation after cochlear implantation is on average 20 dB, we specifically investigated a subset of 16 individuals who had preoperative thresholds at 250 Hz at 65 dB HL or better-assuming that poorer preoperative thresholds would likely not result in aidable acoustic HP (17)(18)(19). Of these 1 recipient with preoperative thresholds 65 dB HL at 250 Hz, 14 had unaided thresholds measured at activation, 7 at 6-months, and 4 at 1-year.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Given that the expected low-frequency threshold elevation after cochlear implantation is on average 20 dB, we specifically investigated a subset of 16 individuals who had preoperative thresholds at 250 Hz at 65 dB HL or better-assuming that poorer preoperative thresholds would likely not result in aidable acoustic HP (17)(18)(19). Of these 1 recipient with preoperative thresholds 65 dB HL at 250 Hz, 14 had unaided thresholds measured at activation, 7 at 6-months, and 4 at 1-year.…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, Roland et al (22) reported the results of the U.S. clinical trial for the Hybrid-L; though they did not report mean or median threshold elevation data, they reported that 66.6% of patients retained aidable hearing postoperatively (lowfrequency thresholds 85 dB HL). Comparable to our Recognizing that the mean threshold elevation is between 15 and 20 dB for long electrodes following CI, if patients begin with thresholds around 80 dB HL, we must assume they will not have aidable hearing preserved postoperatively (17)(18)(19)23,24). Thus, we analyzed a subgroup of patients who had preoperative thresholds at 250 Hz at 65 dB HL or better.…”
Section: Discussionmentioning
confidence: 99%
“…Previous literature (19) reported a subjective improvement 3 months postoperatively using the APHAB questionnaire in EAS users. Because this score remained stable during the 18 months of follow-up of that study, in the present study, the follow-up of the subjective benefit was divided into two parts in the present study.…”
Section: Subjective Benefitmentioning
confidence: 87%
“…To date, the focus of EAS research has been on the degree of postoperative hearing preservation outcomes (Arnoldner et al, 2010;Gantz & Turner, 2003;Gstoettner et al, 2006;James et al, 2006;Kiefer et al, 2005;Lenarz et al, 2006;Gantz, & Tyler, 2010); perception of music (Brockmeier et al, 2010;Dorman, Gifford, Spahr, & McKarns, 2008;Gfeller, Olszewski, Turner, Gantz, & Oleson, 2006;Gfeller et al, 2007;Gifford, Dorman, & Brown, 2010); and functional performance (Driver & Stark, 2010;Gstoettner et al, 2008;Gstoettner et al, 2011;Helbig et al, 2011). In general, results with EAS have been compared with either the cochlear implant used in isolation, or with the preoperative condition with hearing aids.…”
Section: Introductionmentioning
confidence: 99%
“…To date, the focus of EAS research has been on the degree of postoperative hearing preservation outcomes (Arnoldner et al, 2010; Gantz & Turner, 2003; Gstoettner et al, 2006; James et al, 2006; Kiefer et al, 2005; Lenarz et al, 2006; Mukerjee et al, 2012; Skarzynski, Lorens, Piotrowska, & Skarzynski, 2010; von Ilberg et al, 1999; Woodson, Reiss, Turner, Gfeller, & Gantz, 2009) as well as the perceptual benefits of combined electric-acoustic applications for: speech perception (Büchner et al, 2009; Dorman & Gifford, Dorman, & Brown, 2010; Fraysse et al, 2006; Gantz, Turner, Gfeller, & Lowder, 2005; Helbig & Baumann, 2009; James et al, 2005; Lenarz et al, 2009; Lorens, Polak, Piotrowska, & Skarzynski, 2008; Simpson, McDermott, Dowell, Sucher, & Briggs, 2009; Skarzynski et al, 2012; Turner, Gantz, Karsten, Fowler, & Reiss, 2010); localization (Dunn, Perreau, Gantz, & Tyler, 2010); perception of music (Brockmeier et al, 2010; Dorman, Gifford, Spahr, & McKarns, 2008; Gfeller, Olszewski, Turner, Gantz, & Oleson, 2006; Gfeller et al, 2007; Gifford, Dorman, & Brown, 2010); and functional performance (Driver & Stark, 2010; Gstoettner et al, 2008; Gstoettner et al, 2011; Helbig et al, 2011). In general, results with EAS have been compared with either the cochlear implant used in isolation, or with the preoperative condition with hearing aids.…”
Section: Introductionmentioning
confidence: 99%